2014
DOI: 10.1039/c4cc06203e
|View full text |Cite
|
Sign up to set email alerts
|

High solid-state fluorescence in ring-shaped AEE-active tetraphenylsilole derivatives

Abstract: Three ring-shaped AEE-active silole-containing compounds were synthesized by mild condensation reactions. Cyclotrisiloxane compound 1 displays high solid-state quantum yield (Φfl = 0.86) with the fluorescence maximum at 512 nm. This high fluorescence efficiency results mainly from decreased vibrational pathways to fluorescence decay due to the intramolecular C-H···π interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…The solid-state quantum efficiencies for both neat thin-film and single-crystal were measured to be very high (Φ PL‑solid state ∼ 0.78 and 0.81, respectively) using an integrating sphere method. The observed high solid-state quantum yield in the single-crystal is consistent with the presence of multiple strong C–H···π interactions and the absence of π–π interactions in the crystal lattice ( vide supra ), both of which prevents unfavorable fluorescence decays via exciton-vibronic/phonon couplings . Here, we note that similar short-range interactions were also evident in the XRD characterization (a broad peak with 2θ = 16–29° in Figure S14) of the spin-coated neat thin-film, which apparently contributes to the observed high fluorescence efficiency in thin-film phase even though long-range ordering is not present.…”
Section: Results and Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The solid-state quantum efficiencies for both neat thin-film and single-crystal were measured to be very high (Φ PL‑solid state ∼ 0.78 and 0.81, respectively) using an integrating sphere method. The observed high solid-state quantum yield in the single-crystal is consistent with the presence of multiple strong C–H···π interactions and the absence of π–π interactions in the crystal lattice ( vide supra ), both of which prevents unfavorable fluorescence decays via exciton-vibronic/phonon couplings . Here, we note that similar short-range interactions were also evident in the XRD characterization (a broad peak with 2θ = 16–29° in Figure S14) of the spin-coated neat thin-film, which apparently contributes to the observed high fluorescence efficiency in thin-film phase even though long-range ordering is not present.…”
Section: Results and Discussionsupporting
confidence: 77%
“…The observed high solid-state quantum yield in the single-crystal is consistent with the presence of multiple strong C−H•••π interactions and the absence of π−π interactions in the crystal lattice (vide supra), both of which prevents unfavorable fluorescence decays via exciton-vibronic/phonon couplings. 53 Here, we note that similar short-range interactions were also evident in the XRD characterization (a broad peak with 2θ = 16−29°in Figure S14) of the spin-coated neat thin-film, which apparently contributes to the observed high fluorescence efficiency in thin-film phase even though long-range ordering is not present. As shown in Figure 7b, 2EHO-TPA-PE-doped PS and PMMA thin-films showed very similar decay profiles to those observed in the medium-polarity solvents with major prompt decays (0.85 ns (99.75%) and 0.81 ns (98.39%), respectively) followed by minor delayed decay channels (4.09 ns (0.25%) and 2.57 ns (1.61%), respectively).…”
Section: ■ Results and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Siloles–a class of silicon-containing compounds analogous to cyclopentadiene with a remarkably small HOMO–LUMO gap, intrinsically high electron mobility, favorable photophysical properties (near UV to blue light emission peak range: 350–520 nm), and high fluorescence efficienciesare nowadays among the most popular and promising structural building blocks in molecular and polymer-based materials used for manufacturing high-performance electro- and photoluminescent devices. , Given the high degree of their structural variability, their electronic and optical properties can be tuned through a multitude of methods such as polymerization, , attaching conjugating substituents or highly fluorescent groups to the silicon atom, and structural modification of peripheral phenyl moieties . Previously, we demonstrated that well-known silole derivatives combined with highly fluorescent bis(diquinaldinatoalumino) ligands yield compounds displaying a 4- to 6-fold increase in solid-state fluorescence efficiency. Against the backdrop of our latest discovery that highly fluorescent ring-shaped siloxanes containing exclusively silole-based fluorophorstetraphenylsilole (Scheme a) or silafluorene (Scheme b)are easily accessible through a simple cohydrolysis reaction between corresponding dichlorosilole derivatives and dichlorosilane under ambient conditions, , it appeared of interest to us to test if combining different fluorogenic units in this structural framework would have a similar effect on the fluorescence efficiencies of their derivatives. We thus set out to extend our studies of ring-shaped silole derivatives and their photophysical properties by synthesizing a series of near-UV or blue-light-emitting compounds containing well-known fluorogenic units such as phenyl, 1,3-diphenyl-9-silafluorene (Scheme c), 9-silafluorene, and tetraphenylsilole in the siloxane framework.…”
Section: Introductionmentioning
confidence: 99%